Expressing our fallibility: a conception of public reason - Taylor, A (2017)
This thesis is about the reasonable agreement principle, a principle which holds that the exercise of political power must be acceptable to all reasonable citizens in order to be morally legitimate. Though this principle has become popular in contemporary political philosophy, it has been formulated and defended in a variety of often conflicting ways. I argue first that a successful defence of the principle will have to meet three conditions. First, it must explain who reasonable citizens are. Second, it must offer a compelling a rationale for tying the legitimacy of the exercise of political power to what these citizens accept. Third, it must show that the rules or principles that would be acceptable to reasonable citizens are not implausible. In the first part of the thesis, I examine some of the most significant ways in which the principle has been formulated and defended, and argue that none meets these three conditions. In the second part of the thesis, I develop an account of the reasonable agreement principle which can meet these three conditions. I argue that reasonable citizens should be understood as agents in circumstances where their powers of moral judgment operate free of distortions, offer an account of what these circumstances consist in, and suggest that a compelling rationale for the principle can be given when they are understood in this way. I then go on to consider what citizens in such circumstances would accept, arguing that they would accept principles of political morality that express a commitment to the fact that they are fallible choosers of their final ends.